Days - Scheunemann, Pam, 1955- (Edina, Minn. : Abdo Pub., 2001)
Simple text and color photos introduce children to the days of the week and the capital letters with which they are spelled.
"Sandcastle 1.".
"Write on!"--Cover.
Includes index.
1.0.
1.0
K-3
Keywords: Days -- Juvenile literature; English language -- Capitalization -- Juvenile literature; Days; English language -- Capitalization; Days; English language -- Capitalization